ANALISIS PENGEMBANGAN DIMENSI UMKM POTENSIAL DAN MODEL STIMULAN BAGI UMKM DI INDUSTRI BATIK PEKALONGAN JAWA TENGAH - Ariyanti, Yulekhah (Laporan Penelitian dan Pengabdian Masyarakat, 2024)
Usaha Mikro Kecil dan Menengah (UMKM) are building the economy of Indonesia, which accounted for nearly 95% of the number of businesses in Indonesia with the majority classified as household industries. Viewed in terms of quantity of UMKM is reasonable if it has great contribution in the national economy. The present study is oriented to the discovery of quality grade formulation of UMKM, UMKM regroupping which is based on the real problems faced by UMKM and the findings of the initial effective stimulant for the development of UMKM. The object of research conducted in Pekalongan batik centers, with the number of respondents were 58 UMKM. Data collection techniques with menggukan survey through questionnaires with open-ended questions, and with interviews with respondents. The results showed that the respondents (UMKM Batik Pekalongan) grouped into three categories of four health categories of UMKM, namely: (1) 2 UMKM included in category A (excellent), 36 UMKM included in category B (good) and 15 UMKM included in the category C (pretty good). In addition, this study also found regroupping UMKM in accordance with health (quality grade) and the specific problems faced by UMKM. Other research results obtained are formulated type of initial effective stimulant and also as a starting point for further research stage, in order to be validated and adapted to the UMKM contextually targeted to be more effective. Key word: QUALITTY Grade, UMKM, Regroupping, Stimulant